The effect of enforcement on timely loss recognition: Evidence from insider trading laws - Jayaraman, Sudarshan (Journal of Accounting and Economics, 2012)
I use the first-time enforcement of insider trading laws in sixteen countries as a shock to enforcement and examine its influence on timely loss recognition (TLR). Consistent with greater enforcement increasing the usefulness of accounting information in contracts and thereby the demand for higher quality reporting, insider trading enforcement is associated with a significant increase in TLR. No such increase is detected in neighboring non-enforcing countries. In addition to documenting how shocks to enforcement influence financial reporting outcomes, this is also the first study to extend the Khan and Watts (2009) measure of accounting conservatism to a cross-country setting.